2020
DOI: 10.17245/jdapm.2020.20.5.293
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors affecting the difficulty of fiberoptic nasotracheal intubation

Abstract: Background: The success rate of intubation under direct laryngoscopy is greatly influenced by laryngoscopic grade using the Cormack-Lehane classification. However, it is not known whether grade under direct laryngoscopy can also affects the success rate of nasotracheal intubation using a fiberoptic bronchoscpe, so this study investigated the same. In addition, we investigated other factors that influence the success rate of fiberoptic nasotracheal intubation (FNI). Methods: FNI was performed by 18 anesthesiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The nasal route is often used on patients with poor mouth opening or a large tongue as it courses past the nasopharynx with less obstruction by the tongue [ 21 ]. Awake flexible bronchoscope-guided intubation is strongly recommended in patients with anticipated difficult airways [ 2 , 6 , 22 , 23 ]. In this study, orotracheal intubation was performed in anesthetized apneic patients with normal airways as it is considered more difficult than nasal intubation of the awake patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nasal route is often used on patients with poor mouth opening or a large tongue as it courses past the nasopharynx with less obstruction by the tongue [ 21 ]. Awake flexible bronchoscope-guided intubation is strongly recommended in patients with anticipated difficult airways [ 2 , 6 , 22 , 23 ]. In this study, orotracheal intubation was performed in anesthetized apneic patients with normal airways as it is considered more difficult than nasal intubation of the awake patient.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed anesthesiologists achieved competence (first-attempt intubation success rates > 90% and intubation time of ≤ 2 minutes) in fiberoptic laryngoscopy and intubation in anesthetized patients with normal airways after 10 procedures [ 22 ], and all the trainees learned at the same rate. Several reasons may explain the disparate findings between the prior report and the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the limitation of the manikin, the tongue was unable to be inflated to simulate tongue edema. At the same time, it also cannot simulate the clinical scenario of sputum and secretions blocking the view field ( 36 ), so the advantage of multimodal tracheal intubation aids was not fully realized. The initial prototype MEIAD used in this study has not yet been put into production and clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…However, the surgical procedure, including tracheostomy and a submental approach, may have potential complications, including bleeding, infection, and hypertrophic scarring [12], which can be relatively notable in patients who undergo elective orthognathic surgery. Fiberoptic nasotracheal intubation was also considered; however, anatomical abnormalities, bleeding, and secretion in the oral and pharyngeal cavity can cause the failure of intubation or accidental intracranial placement of the fiberoptic scope itself [16,19]. Therefore, we devised a simple and safe technique using a balloon catheter as an alternative to fiberoptic intubation.…”
Section: Figure 3: Balloon Catheter-guided Nasotracheal Intubation Pr...mentioning
confidence: 99%
“…Submental intubation can also cause hemorrhage, infection, orocutaneous fistula, and injury to the sublingual or lingual nerves [8,12]. Fiberoptic nasotracheal intubation is a standard technique for the management of patients with problematic airways [13]; however, the failure rate of fiberoptic intubation when performed by skillful and experienced anesthesiologists is still 4-5% [14], which is caused by anatomical abnormalities, bleeding, and secretions in the oral and pharyngeal cavities [15,16]. Thus, alternative options for nasotracheal intubation in patients with basal skull defects are needed.…”
Section: Introductionmentioning
confidence: 99%